FRI0498 Comparative study of the treatment of refractory cystoid macular oedema to conventional immunosuppressive therapy: tocilizumab vs anti-tnf. multicenter study of 59 patients. (12th June 2018) - Martín-Varillas, J.L.; Calvo-Río, V.; Demetrio-Pablo, R.; Atienza-Mateo, B.; Loricera, J.; Hernández, M.V.; Adán, A.; Mesquida, M.; Insua, S.; Herreras, J.M.; Maíz, O.; Blanco, A.; et al.
Abstract : Background: Cystoid macular oedema (CME) is the most serious complication of uveitis. This potentially severe complication may lead to irreversible visual loss. 1–2 Objectives: To compare efficacy and safety of Tocilizumab (TCZ) vs. Anti-TNF-α drugs in patients with refractory CME to conventional immunosuppressant (IS). Methods: Multicenter study of patients with refractory CME to treatment with glucocorticoids and at least 1 conventional IS. The main objective was the improvement of macular thickness. Secondary objectives were the enhancement in best corrected visual acuity (BCVA) and the degree of ocular inflammatory activity. Results: 59 patients/112 affected eyes. Causes of uveitis were: Behçet's disease (n=41), Birdshot's retinochoroidopathy (n=4), Juvenile Idiopathic Arthritis (n=9), Sarcoidosis (n=1) and idiopathic (n=4). No significant differences were observed at baseline in both groups (TCZ vs Anti-TNF-α) in sex (♂/♀; 8/17 vs. 15/19), mean age (35.6±18.9 vs 40.0±9.1), BCVA (0.40±0.31 vs. 0.48±0.31), Tyndall (1 [0–1] vs. 1 [0–2]), vitritis (1 [0–2] vs. 1 [0–3]) and macular thickness (431.8±165.9 vs. 397.1±138.1) (table 1). 25 patients were treated with TCZ as follows: 8 mg/kg/4 weeks (n=24) and 162 mg sc/2 weeks (n=1). Anti-TNF-α therapy was used in the remaining 34 as follows: IFX (n=12) (5 mg/kg 0, 2 y 6 weeks and every 4–8 weeks) and ADA (n=22) (40 mg/sc/2 weeks). We observed a rapid and sustained improvement in macular thickness after 1 year follow-up in both groups, without objectifying significant differences between them. In the same way, secondary ocular parameters also improved (table 1). Conclusions: TCZ and Anti-TNF-α are effective in the treatment of CME refractory to conventional therapy. References: [1] Calvo-Río V, Blanco R, Beltrán E, et al. Anti-TNF-alfa therapy in patients with refractory uveitis due to Behçet's disease: a 1-year-follow-up study of 124 patients. Rheumatol. 2014;53(12):2223–31. [2] Calvo-Río V, Blanco R, Santos-Gómez M, et al. Efficacy of anti-il6-receptor tocilizumab in refractory cystoid macular edema of Birdshot retinochoroidopathy report of two cases and literature review. Ocul Immunol Inflamm. 2017;25(5):604–609. Disclosure of Interest: None declared